Feasibility Analysis and Break Even Point Celery Farming (Apium graveolens L.) Hydroponic Deep Flow Technique (DFT) System (Case Study on a Farmer in Kayuambon Village, Lembang District, West Bandung Regency) - Tito Hardiyanto; Rena Riswana; Arneta Arneta (International Journal of Quantitative Research and Modeling, 2023)
Medicinal properties. The celery plant also contains many apiin glycosides (flavone glycosides, isoquercetin, and umbelliferons. It also contains, mannite, inocytes, asparagine, glutamine, choline, linamarose, pro vitamin A, vitamin C, and B. This study aims to determine the cost, R/C Ratio, break-even point (BEP) of celery hydroponic farming system with deep flow technique (DFT). The analysis method used in this study is quantitative analysis by calculating and detailing the analysis of costs, income and receipts, feasibility, and break-even points. The results showed that the cost of the hydroponic agricultural system was Rp. 2,213,720.6. The R/C Ratio is 1.01, so the agricultural system is feasible. The break-even point (BEP) for receipts amounted to Rp. 2,160,006.45 while real receipts amounted to Rp. 2,224,800. This means that this agricultural system still benefits Rp. 64. 733.55. The break-even point for production is 184.48 Kg, while the actual production is 185.4 Kg. This means that production provides a benefit of 0.92 Kg. Break-even point selling price is Rp. 11,940.24/Kg while the actual selling price is Rp. 12,000/Kg. This agricultural system provides benefits of Rp. 60/Kg.